Impact of intermediate-dose tertiary prophylaxis on quality of life and psychological aspects of adult patients with severe/moderate hemophilia A - Hua Gao; Jia Liu; Shiqiu Zhou; Jing Gao; Jing Tan; Rong Chen (Hematology)
Objectives Whether intermediate-dose tertiary prophylaxis can improve quality of life and psychological health in adults with severe/moderate hemophilia A has not been determined. This research aims to explore the impact of intermediate-dose tertiary prophylaxis with recombinant human FVIII (rhFVIII) on quality of life, anxiety and depression in such individuals transitioned from on-demand treatment.Methods This retrospective analysis collected data from July 2019 to July 2022. Haemophilia Quality of Life Questionnaire for Adults (HAEMO-QoL-A), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) were compared before and after prophylaxis. Additionally, functional independence and joint status were analyzed at the end of the 3-year prophylaxis period, as well as their correlations with HAEMO-QoL-A, PHQ-9, and GAD-7.Results The HAEMO-QoL-A total score decreased after prophylaxis (pre-prophylaxis: 88.90 ± 33.38 vs. post-prophylaxis: 79.59 ± 22.89) (P = 0.016). The mean PHQ-9 scores before and after prophylaxis were 4.44 ± 4.63 and 5.56 ± 4.30 (P = 0.058), respectively, while the mean GAD-7 scores were 3.15 ± 3.84 and 4.44 ± 3.99 (P = 0.016). Significant correlations were observed for HAEMO-QoL-A with functional independence (P < 0.001), mood and emotions with age (P = 0.032), PHQ-9 scores with knee joint rehabilitation scores (P = 0.047), and GAD-7 scores with treatment experience and ankle joint rehabilitation scores (P = 0.029, P = 0.039).Conclusion Intermediate-dose tertiary prophylaxis with rhFVIII can improve quality of life but not relieve anxiety and depression in adults with severe/moderate hemophilia A. Better functional independence correlates with improved quality of life. Gait and age also influence the quality of life to some extent. We need to undertake anxiety and depression screening and provide psychological treatment when necessary.